Analisis Fungsi dan Makna Wazan Af'ala Dalam Al Quran Surat Al Mu’minun - Ngatipan Ngatipan; Kelik Ali Usman (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The verses of the Koran themselves contain absolute and final truth as when the book was revealed, while the truth of the interpretation of the text of the Koran is relative, so that the meanings of these verses can continue to be reproduced and developed according to the development of civilization and human needs themselves. Using library research methods, this research seeks to examine the function and meaning of the verses constructed from the form (ṣigah) fi'il 'alā Wazni Af'ala in Surah Al Mukminun. Based on the research results, several things can be concluded, First; 59 words or 59 places were found, both of isim and fi'il types whose word structure came from wazan af'ala. Second ; Of the 59 words originating from the wazan af'ala structure in Surah Al Mu'minun, it was found that 0.53% (32 words) contained the Lī Al Ta'diyyah function. Of the remainder, 2 words contain the meaning function للدخول في الشّيء (entering into something), 8 words contain the function لوجود مااشْتَقَّ منه الفعلُ في الفاعل (appearance origin of fi'il in fā'il), the next 4 words contain the function للمُبالَغَة (exaggerating the meaning of fi'il ), 2 words contain the function لوِجْدانِ الشيءِ في صِفةٍ (find something in nature), 6 words contain the function للصَّيْرُورة (change into), 3 words contain the function للتَّعْريْ ض (show off), 1 word contains the function للحَيْنونَة (arriving time), and 1 word contains للسَّلْب (withdraw or remove) function.